The impact of technical change and profit on investment in Australian manufacturing - Bloch, Harry; Courvisanos, J.; Mangano, M. (Routledge, 2011)
This paper combines W.E.G. Salter's analysis of capital-embodied technical change with Kalecki's analysis of financing investment from retained profits to provide a Post Keynesian model of investment with process innovation, which is applied to data from Australian manufacturing industries. The approach to process innovation taken in this study is to identify new capital stock introduced through physical investment, which results in the older vintage stock being decommissioned as technologically obsolete. In the estimated model, the profit factor is used as a measure of the ability to invest, and the rate of labour productivity growth factor reveals the inducement to invest as this rate acts as a proxy for technical change in the Kaleckian investment-ordering model. The two factors combine to explain the accumulation process, both level and variability, and its link to technical change. In conclusion, this paper demonstrates that investment, incorporating technical change, enables industries to become sustainable into the uncertain future with varying states of investment instability. …technical progress cannot be regarded as automatic and independent of accumulation. (Salter, 1966, p. 72)